A Study On Accounting Conservatism Of Capital-Raising Corporations - Hong, Soonwook (Journal of Applied Business Research, 2017)
Various factors affect conservative accounting of corporations. Most of all, this paper focuses on the factor of corporate capital raising. One of the important roles of conservatism is that companies conduct conservative accounting to cut the agency costs due to information asymmetry. Managers may desire excellent management performance and stable financial condition. Depending on circumstances, they seek to improve management performance and financial condition by choosing a proper accounting method. That is, they have incentives to carry out less conservative accounting. Companies that raise capital may have stronger incentives to take such an accounting method. On the contrary, if a capital market monitoring system works properly, corporations would conduct conservative accounting to reduce the agency costs. The results of the empirical analysis reveals that the Korean listed companies raising capital choose less conservative accounting than those that do not raise capital. This indicates companies without financing conduct conservative accounting more than those with.
Keywords: Conservatism; Capital Raising; Accounting Choice; Information Asymmetry; Agency Cost; Earnings Management